Re-organizing the present site management team of the Contractor BUCG-ABC JV in the BRAC University new campus project - Brac University; Brac University (Brac University, 2023)
This record consists of general correspondence regarding re-organizing the present site management team of the Contractor BUCG-ABC JV in the BRAC University new campus project.